Optimisme Pertumbuhan Kredit Perbankan di Tengah Ketidakpastian Ekonomi Global - Hendiyoga pranata; Aby Hanandany (New Economy, 2025)
This research aims to analyze the optimism of banking credit growth in Indonesia amid global economic uncertainty affecting credit demand and distribution. The method used is library research with a descriptive qualitative approach, which examines various literature, official reports from Bank Indonesia, the Financial Services Authority (OJK), as well as current statistical data and economic articles. The research results show that although credit growth in 2025 experienced a slowdown with an annual rate of 8.88% in April 2025, the investment sector and the productive sector remained the main drivers of credit growth. Accommodative monetary policies, such as lowering the benchmark interest rate and strengthening macroprudential policies, provide significant support for credit distribution. In addition, coordination between financial authorities also helps maintain the stability of the national financial system. In conclusion, despite the challenges posed by the uncertain global economic conditions, strong domestic economic fundamentals and appropriate policies are the main factors underlying the optimism for Indonesia's banking credit growth in 2025.